Implementation of The Independent Curriculum Trough Authentic Learning in Fiqh Subject at Madrasah Tsanawiyah Qita - Shobihatul Fitroh Noviyanti; Ana A’yun Qurrota Amiliya; Shafiyah Amatullah; Malihatul Mu’auwwanah (International Journal of Education Management and Religion, 2025)
This study aims to analyze the implementation of the Independent Curriculum at QITA Junior High School, especially in the Fiqh subject. A qualitative method was employed, utilizing observation, interviews, and documentation involving teachers and the learning process. The findings indicate that QITA School has successfully implemented the Independent Curriculum with authentic, student-centered learning that integrates religious values with technology and science. Project-based activities, such as video lectures, enhance creativity and engagement. Regulated use of cellphones supports focus in learning. The implications suggest that such implementation can serve as a model for other Islamic schools seeking innovative approaches to religious education